Profile of New Patients with Candida Infection in Skin and Nail - Shinta Dewi Rahmadhani Soetojo; Linda Astari (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Candidiasis are different groups of infection which is caused by Candida albicans and other spesies in the genus Candida can invade hair, skin, nail, mucous membrane and systemic. Purpose: To evaluate profile, process of diagnosis, treatment and follow up of patient with candida infection on the skin and nails. Methods: This research was performed retrospectively to new patients with candida infection of skin and nails in period of 2011-2013. Result: There were 137 patients in period 2011-2013, which are 114 new patients with infection in skin and 23 patients with nails involvement. Most of them were women, respectively in 2011 (54.3%) 2012 (80%) and 2013 (56.6%). Most types of skin disorder is candida intertriginosa (62.2%) and candidiasis of skin and nails (91.3%). Conclusion: Overview of new cases of candida infections of skin and nails tend to decrease.Key words: Candidiasis spp, candida infection of skin and nails.